Altered collecting duct adenylyl cyclase content in collecting duct endothelin-1 knockout mice - Kohan Donald E; Stricklett Peter K; Strait Kevin A (BMC Nephrology, 2007)
Abstract Background Endothelin-1 (ET-1) inhibition of vasopressin (AVP)-stimulated water reabsorption by the inner medullary collecting duct (IMCD) is associated with reduced cAMP accumulation. To determine the effect of ET-1 deficiency, AVP-stimulated cAMP responsiveness was assessed in IMCD from mice with collecting duct-specific deletion of ET-1 (CD ET-1 KO) and from control animals. Methods Cyclic AMP production, adenylyl cyclase (AC) mRNA, and AC protein were measured in acutely isolated IMCD. Results CD ET-1 KO IMCD had enhanced AVP-stimulated cAMP accumulation. Inhibition of calcium-stimulated AC using BAPTA did not prevent enhanced AVP responsiveness in CD ET-1 KO IMCD. Factors known to be modified by ET-1, including nitric oxide, cyclooxygenase metabolites, and superoxide did not affect the increased AVP responsiveness of CD ET-1 KO IMCD. Differential V2 receptor or G-protein activity was not involved since CD ET-1 KO IMCD had increased cAMP accumulation in response to forskolin and/or cholera toxin. CD ET-1 KO did not affect mRNA or protein levels of AC3, one of the major known collecting duct AC isoforms. However, the other known major collecting duct AC isoform (AC5/6) did have increased protein levels in CD ET-1 KO IMCD, although AC5 (weak signal) and 6 mRNA levels were unchanged. Conclusion ET-1 deficiency increases IMCD AC5/6 content, an effect that may synergize with acute ET-1 inhibition of AVP-stimulated cAMP accumulation.